Evaluation of Government Policy in Protecting Protected Animals in Tesso Nilo National Park, Pelalawan Regency - Syaprianto, Syaprianto; Herman, Herman (Jurnal Ilmiah Muqoddimah: Jurnal Ilmu Sosial, Politik dan Hummaniora, 2025)
This study aimed to know the protection of protected animals in Tesso Nilo National Park, Pelalawan Regency. The Tesso Nilo forest is a habitat for endangered animals, namely the Sumatran tiger (Panthera tigris sumatrae) and the Sumatran elephant (Elephas maximus sumatranus). Sumatran tigers and Sumatran elephants are protected animals. The encroachment of the Tesso Nilo National Park (TNTN) area has long occurred and has been converted into plantations and residential areas. The results of this study indicate that protecting protected animals in Tesso Nilo National Park Pelalawan Regency has been implemented. However, it has not been implemented effectively because there is still poaching, deforestation, and various other activities that can threaten the extinction of these animals. Some of the obstacles faced by the Tesso Nilo National Park Office in protecting protected animals are multidimensional, including internal problems such as limited resources and budgets and external challenges such as habitat destruction, poaching, and conflicts with communities. To overcome these barriers, closer collaboration between the government, conservation agencies, local communities, and the private sector is needed to improve the effectiveness of conserving and managing conservation areas in TNTN.